Comparative Analysis of Time Series Trends in the Financial Performance of the Food Industry at Campina Ice Cream Industry, Ultrajaya Milk Industry, Diamond Food Indonesia, and Garudafood Putra Putri Jaya for the Period 2021–2024 - Daariin Dewi Nabiilah; Nur Imroatus Sholikah; Adinda Nibros Zahira Fasya; Kemberly Susana Kambuaya; Cholis Hidayati (Tinta Emas Institute, 2025)
This study aims to analyze and compare the financial performance of food and beverage companies listed on the Indonesia Stock Exchange using time series and cross section approaches. The research examines PT Campina Ice Cream Industry Tbk, PT Ultrajaya Milk Industry Tbk, PT Diamond Food Indonesia Tbk, and PT Garudafood Putra Putri Jaya Tbk during the 2021–2024 period. A quantitative descriptive-comparative method is applied using secondary data from audited annual financial statements. Financial performance is assessed through liquidity, activity, solvency, and profitability ratios. The results indicate that PT Campina Ice Cream Industry Tbk shows the strongest liquidity and stable profitability, while PT Ultrajaya Milk Industry Tbk records the highest profit margin despite ratio fluctuations. PT Diamond Food Indonesia Tbk demonstrates moderate and stable performance, while PT Garudafood Putra Putri Jaya Tbk excels in asset utilization and interest coverage. Overall, the analysis reveals differences in financial strengths and weaknesses that reflect each company's competitive position within the food and beverage industry.